2022
DOI: 10.1108/ijchm-09-2021-1126
|View full text |Cite
|
Sign up to set email alerts
|

Effects of history, location and size of ethnic enclaves and ethnic restaurants on authentic cultural gastronomic experiences

Abstract: Purpose The extant gastronomy literature has rarely examined a connection between authentic gastronomic experiences and destinations. Specifically, ethnic enclaves, which are unique gastronomic and cultural destinations providing ethnic cuisine and cultural experiences to visitors, have been under-researched. Thus, this study aims to address this knowledge gap. Design/methodology/approach Using a 2 (history: long vs short) × 2 (location: Central Business District vs rural; main street vs alleyway) × 2 size/o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…Third, this study contributes to the restaurant authenticity literature. Previous studies seem to neglect the importance of external environmental factors (Song and Kim, 2022), particularly those related to signage language. Among the limited academic attempts, foreign language shown on the restaurant signs did not increase diners’ authenticity perception (Magnini et al , 2011).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Third, this study contributes to the restaurant authenticity literature. Previous studies seem to neglect the importance of external environmental factors (Song and Kim, 2022), particularly those related to signage language. Among the limited academic attempts, foreign language shown on the restaurant signs did not increase diners’ authenticity perception (Magnini et al , 2011).…”
Section: Discussionmentioning
confidence: 99%
“…For example, De Vries and Go (2017) reported external façade contributes to restaurant authenticity. However, scholars found that both the foreign language displayed on outdoor signboard (Magnini et al , 2011) and the area (city center vs rural area) that the ethnic restaurant is located in Song and Kim (2022) do not contribute to the level of restaurant authenticity. As a result, the theoretical knowledge in this area is still limited, and our study aims to shed light on this understudied area.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The study proposed by Song and Kim (2022) deals with the relation between gastronomic experiences and destinations, by focusing on ethnic enclaves. The authors develop two experiments by leveraging a sample of 557 British consumers to test the effect of history, location and size of ethnic enclaves and ethnic restaurants on consumers' authentic cultural and gastronomic experiences.…”
Section: Value and Image Of Gastronomy Experiences By Restaurants And...mentioning
confidence: 99%